2016
DOI: 10.1002/lary.26379
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the efficacy of endoscopic tympanoplasty and microscopic tympanoplasty: A systematic review and meta‐analysis

Abstract: Our up-to-date review evidences the comparable tympanic membrane closure rates and hearing results for endoscopic and microscopic tympanoplasty. Patients receiving endoscopic tympanoplasty have a lower canalplasty rate and more desirable cosmetic result than do those receiving microscopic tympanoplasty. Laryngoscope, 127:1890-1896, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
101
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(116 citation statements)
references
References 27 publications
14
101
1
Order By: Relevance
“…Our findings were similar to those presented in the previously published meta‐analysis. In contrast to the former publication, specifically regarding this topic, the present search yielded an additional three more randomised controlled trials which allowed us to arrange subgroups of RCTs. To rate the evidence of every statement, the GRADE approach was used (Table ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings were similar to those presented in the previously published meta‐analysis. In contrast to the former publication, specifically regarding this topic, the present search yielded an additional three more randomised controlled trials which allowed us to arrange subgroups of RCTs. To rate the evidence of every statement, the GRADE approach was used (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, a superbly written meta-analysis was published which collected evidence regarding both endoscopic and microscopic type I tympanoplasty. 7 Since this topic is of particularly high interest, several new studies, including high-quality randomised controlled trials (RCTs), have been recently published. The large body of evidence accumulated proved inspirational, resulting in our intensive review of the plethora of recently published literature.…”
Section: Objectivesmentioning
confidence: 99%
“…18 In the present study, patients were between 15-55 years of age. The most common age group of patients in our study was the third decade ( 19 They found that pooled canalplasty rate of endoscopic tympanoplasty was significantly lower than that of microscopic tympanoplasty. Patients undergoing endoscopic tympanoplasty had a more desirable cosmetic result than with microscopic tympanoplasty.…”
Section: Discussionmentioning
confidence: 62%
“…[1,3,10,11] Two systematic reviews revealed that graft survival rate and hearing outcomes following ET were comparable with CMT. [12,15] In the qualitative analysis of Lee et al [15] , the graft survival rate in ET ranged from 83% to 100%, which was similar to that in CMT according to the studies included in their meta-analysis. The graft survival rate seems to be affected by the grafting technique rather than the type of surgical approach, although most of the studies regarding the outcomes of ET utilized an underlay grafting technique during ET, which may constitute a potential publication bias [15] .…”
Section: Discussionmentioning
confidence: 82%
“…[7][8][9] In recent studies, ET has also been demonstrated with favorable results as a minimally invasive surgery. [10][11][12] ET enables a wider view with varying angles of view, and does not require canalplasty, postauricular incision and general anesthesia; hence, the operative time is shorter than with conventional techniques. The minimally invasive nature of gery is usually affected by the width, tortuosity and bony overhangs of the ear canal, therefore canalplasty is often performed to improve the vision.…”
Section: Introductionmentioning
confidence: 99%